Ethnic slurs as war names in the Zimbabwean liberation war - Barnes, Lawrie A.; Pfukwa, Charles (Routledge, 2021)
The Zimbabwean war of liberation raged from 1966 until 1979. During that time many combatants assumed (or were given) noms de guerre. From a collection of more than 4800 of these war names we found that ethnic slurs comprised 9% of the total. One name in particular, Mabhunu, an adaptation of Boer, was especially common among ethnic slurs. The war names were seen to be important by the participants; they created images to be projected to the world at large or reflections constructed by outsiders.